Emergency Contraceptive Pill Use and its Impact on Condom Utilization Among University Students: A Cross-Sectional Study - Genemo ES; Korsa AT; Bayisa HG (Dove Medical Press, 2022)
Edao Sado Genemo,1 Ayana Tadesse Korsa,2 Habte Gebeyehu Bayisa2 1Department of Pharmacy (Pharmacoepidemiology and Social Pharmacy Unit), Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 2Department of Pharmacy (Clinical Pharmacy Unit), Institute of Health Sciences, Wollega University, Nekemte, EthiopiaCorrespondence: Ayana Tadesse Korsa, Department of Pharmacy, Institute of Health Sciences, Wollega University, P.O Box 395, Nekemte, Ethiopia, Tel +251912143175, Email Korsa.ayana02@gmail.com; ayanat@wollegauniversity.edu.etPurpose: Emergency contraceptive pills (ECPs) prevent unplanned pregnancy but not sexually transmitted infections (STIs), and the practice of ECP may affect condom use. This study, therefore, aimed to assess ECP use and its impact on condom utilization among female students of private universities in Nekemte town, western Ethiopia.Methods: An institution-based cross-sectional study was conducted on 400 female students in three different private universities from February 1 to 28, 2019. Study samples were selected through simple random sampling technique. Data collected from a structured self-administered questionnaire were analyzed using SPSS version 23.0. Bivariate and multivariate logistic regression were performed to determine factors associated with condom utilization, and statistical significance was set at 95% confidence interval (CI) using a p-value of < 0.05 as a cutoff point.Results: The response rate was 95.3% (381/400). Overall, 51.4% (196/381; 95% CI = 45.1%, 57.7%) had awareness of ECP. Besides, 186 (48.8%) students reported history of sexual intercourse, of which 115 (61.8%) have ever practiced ECP and 96 (51.6%) have ever used condom. However, only 11 (5.9%) have ever utilized ECP and condom concurrently. Use of ECPs (adjusted odds ratio (AOR) = 0.32; 95% CI = 0.164, 0.632; p = 0.001), belief that condom prevents STI (AOR = 3.17; 95% CI = 1.045, 8.646; p = 0.041) and thought that ECP does not prevent STI (AOR = 2.217; 95% CI = 1.172, 4.59; p = 0.032) had statistically significant association with condom utilization.Conclusion: The practice of ECP was average, while dual method contraception use was low in the study area. History of ECP use and beliefs that ECP is not effective to prevent STI or condom protects against STI were factors associated with condom use.Keywords: condom, emergency contraception, female students, Nekemte